Pharmacist’s Strategies in Treating Asthma Bronchiale Outpatien - Amelia Lorensia; Endang Wahjuningsih; Benny Canggih; Natalia Lisiska (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2011)
ABSTRACT Asthma is one of the major health problems in the world. Actual asthma symptoms can be treated and controlled, so that most patients can prevent the onset of symptoms throughout the day, to prevent a serious attack. Pharmacists play a role in pharmaceutical care that aims to find health care system needed to improve drug therapy of complex and significant value of drug-related morbidity and mortality, functions to improve pharmacotherapy outcomes and quality of life of patients with asthma. The patient's belief about health and illness and related behaviors are also very important to the effectiveness of pharmaceutical care. Objective research to study the role of pharmacists in pharmaceutical care in the treatment of outpatient asthma bronchiale. The type of study was cross-sectional. The number of respondents recruited was 22 patients. In this study data were obtained by direct interview using a form of data collection, accompanied by observations of the patients. Result research Patients involved in this study were 22. The total numbers of DRPs were 20 cases (problem-based) and 23 cases (cause-based). The class of drugs causing most DRPs was beta-2 agonist. The subjective perceptions of symptoms experienced by the majority of patients with asthma were: shortness of breath (100%), wheezing sound (90%), fatigue and difficulty sleeping (85%). The cognitive aspect of illness perceived by the patients regarding identity, cause of illness and cure or control was correct, but those concerning consequences and timeline were still lacking. This study demonstrates that the role of pharmacists in pharmaceutical care in ambulatory asthma patients has a nature of direct counseling to patients and monitoring. Monitoring of patients on a regular basis and analysis of the occurrence of drug-related problems might help the patients to get effective, safe and rational treatment. Keywords: asthma, pharmaceutical care, drug related problems, illness perception ABSTRAK Asma adalah salah satu masalah kesehatan utama dunia. Gejala asma yang sebenarnya dapat diobati dan dikendalikan sehingga mencegah serangan yang serius. Apoteker perlu memainkan perannya dalam pharmaceutical care (pelayanan kefarmasian) yang bertujuan untuk menemukan sistem perawatan kesehatan yang diperlukan untuk meningkatkan nilai terapi obat kompleks dan signifikan obat morbiditas dan mortalitas terkait, berfungsi untuk meningkatkan hasil farmakoterapi dan kualitas hidup pasien asma. Persepsi pasien terhadap kesehatan dan penyakit terkait juga sangat penting utnuk efektifitas perawatan farmasi. Penelitian ini bertujuan untuk mempelajari peran apoteker dalam perawatan farmasi dalam pengobatan rawat jalan asma bronkial. Jenis penelitian ini adalah cross-sectional. Jumlah responden 22 Pasien. Data diperoleh dengan wawancara langsung untuk mengumpulkan data, disertai dengan pengamatan dari pasien. Hasil: jumlah drug-related problems (DRPs) adalah 20 kasus (problem based) dan 23 kasus (caused-based). Kelas obat yang menyebabkan DRPs terbanyak adalah beta-2 agonis. Pesrsepsi subjektif dari gejala yang dialami oleh sebagian besar pasien dengan asma adalah : sesak napas (100%), suara mengi (90%), kelelahan dan kesulitan tidur (85%). Aspek kognitif penyakit yang dirasakan oleh pasien mengenai identitas, penyebab penyakit dan menyembuhkan atau mengendalikan penyakit adalah benar, tetapi tentang konsekuensi dan timeline masih kurang. Penelitian ini menunjukkan bahwa peran apoteker dalam perawatan farmasi pada pasien asma rawat jalan memiliki sifat konseling langsung ke pasien dan pemantauan. Pemantauan pasien secara teratur dan analisis terjadinya DRPs untuk membantu pasien mendapatkan pengobatan yang efektif, aman dan rasional. Kata kunci: asma, pelayanan kefarmasian, drug-related problems, persepsi sakit